Method for preparing steam-cured ceramsite from fly ash

By calcining fly ash and modifying titanate, combined with the mixing and treatment of multiple materials, high-strength and lightweight steamed ceramids are prepared, which solves the problems of limited utilization channels of fly ash and insufficient performance of ceramids, and meets the needs of construction and sewage treatment fields.

CN119899015APending Publication Date: 2025-04-29XIAN CONSTR SCI & TECH UNIV ARCHITECTURAL DESIGN INST
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510053658.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

In the prior art, fly ash has limited access, and the strength and lightness of the ceramic particles are insufficient, making it difficult to meet the high-performance needs in the fields of construction and sewage treatment.

Method used

After calcining the fly ash, titanate is added to compound modification, and mixed with cement, lime, gypsum, expanded perlite powder, aluminum fluoride and hydrogen peroxide, the mixture is formed and sprayed with water in a round pot granulator to obtain primary ceramic granules. Then soak, dry, nourish and steam in the exciter to obtain high-strength and lightweight steamed ceramic granules.

Benefits of technology

It improves the volcanic ash reaction capacity and compatibility with concrete, enhances the strength and lightness of the ceramic particles, and meets high-performance needs in areas such as construction and sewage treatment.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a method for preparing steam-cured ceramsite from fly ash, and belongs to the technical field of ceramsite processing. The invention discloses a method for preparing steam-cured ceramsite from fly ash, which comprises the following steps: (1) calcining fly ash, and adding titanate for composite modification to obtain pretreated fly ash; (2) mixing the raw materials in proportion to form a mixture, placing the mixture in a round pot granulator, and spraying a proper amount of water on the mixture to prepare primary ceramsite; (3) soaking the ceramsite in an exciting agent; and (4) drying, nursing and steam-curing to obtain the ceramsite. The ceramsite prepared by the preparation method disclosed by the invention has the properties of low density, light weight and high compressive strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramsite processing and relates to a method for preparing steam-cured ceramsite from fly ash. Background Art

[0002] Fly ash is solid waste discharged from coal-fired power plants and is the country's largest source of solid waste pollution. The main oxide components of fly ash are: SiO2, Al2O3, FeO, Fe2O3, CaO, TiO2, etc. At present, the main utilization of fly ash includes cement, concrete and building materials production, among which the total volume of aggregate accounts for 60% to 80% of the volume of concrete.

[0003] Ceramic aggregate is a kind of artificial lightweight aggregate. The raw materials are mainly composed of clay, various shales, slag, coal gangue, fly ash, biological sludge and riverbed mud. After being crushed into particles or ground into balls, they are sintered or cured, and finally form a ceramic granular material with a hard shell on the outside, a layer of barrier glaze on the surface that can block water and air, and a honeycomb porous grid structure inside. Ceramic aggregate has high strength, low density, large specific surface area, high porosity, strong adsorption and interception ability, good thermal stability, corrosion resistance, water and air insulation, and thermal insulation. It is widely used in construction engineering, landscaping, sewage treatment and other fields. Summary of the invention

[0004] The invention relates to a method for preparing steam-cured ceramsite from fly ash, and belongs to the technical field of ceramsite processing. The invention discloses a method for preparing steam-cured ceramsite from fly ash, which comprises the following steps: (1) calcining the fly ash first, and then adding titanate for composite modification, i.e. pre-treating the fly ash; (2) mixing the raw materials in proportion to form a mixture, and placing it in a round pot granulator, and spraying an appropriate amount of water on the mixture to obtain primary ceramsite; (3) soaking the ceramsite in an activator; (4) drying, curing, and steaming to obtain the ceramsite. The ceramsite prepared by the preparation method of the invention has the properties of low density, light weight, and high compressive strength.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A method for preparing steam-cured ceramsite from fly ash, wherein the method for preparing steam-cured ceramsite from fly ash comprises the following specific steps:

[0007] (1) First, the fly ash is calcined, then titanate is added and stirred, then the mixture is heated and dried, and sieved to obtain the pretreated fly ash;

[0008] (2) pre-treating fly ash, cement, lime, gypsum, expanded perlite powder, aluminum fluoride and hydrogen peroxide to form a mixture, and placing it in a round pot granulator, while spraying water on the surface of the mixture, the mass of the sprayed water is 10-15% of the mixture, and the mixture is rolled to obtain primary ceramsite;

[0009] (3) Soaking the primary ceramsite in an activator;

[0010] (4) After drying, curing and steaming, expanded clay is obtained.

[0011] Furthermore, in the step (1), the calcination temperature and time are 800-1000° C. and 20-30 min respectively, and the mass ratio of the titanate to the fly ash is 1:35-45, wherein the titanate is a titanate coupling agent.

[0012] Furthermore, in the step (1), the speed and time of stirring are 1200-1500 r / min and 30-40 min respectively, the temperature and time of heating and drying are 80-100° C. and 60-90 min respectively, and the mesh size of sieving is 200-400 mesh.

[0013] Furthermore, in the step (2), the mass ratio of the pretreated fly ash, cement, lime, gypsum, expanded perlite powder, aluminum fluoride and hydrogen peroxide is 60-80:20-40:2-14:2-10:4-8:2-5:20-30.

[0014] Furthermore, in the step (2), the inclination and rotation speed of the round pot granulator are 35-50° and 33-35 r / min respectively.

[0015] Furthermore, the specific method of spraying water in step (2) is: one spraying lasts about 1 second, each spraying interval is 5 seconds, the rolling time of the mixture is 1-2 minutes, and the particle size of the primary ceramsite is 4-6 mm.

[0016] Furthermore, in the step (3), the activator is a sodium silicate solution with a mass fraction of 30-45%, and the soaking time is 30-60 minutes.

[0017] Furthermore, the specific method of drying in step (4) is: placing the primary ceramsite in an oven at 100-120° C. for drying for 1-2 hours, and then taking it out and cooling it to room temperature.

[0018] Furthermore, the specific method of curing in step (4) is: placing the dried primary ceramsite in a lighted place without moving it, and curing it naturally for 7-10 hours.

[0019] Furthermore, the specific method of steam curing in step (4) is: steam curing the cured primary ceramsite under high temperature steam conditions of 120-160° C. for 6-12 hours.

[0020] Beneficial effects of the present invention:

[0021] 1. After calcination, fly ash changes its crystal structure, increases its glass content and activity, and enhances its volcanic ash reactivity in concrete. At the same time, it is composite-modified with titanate to improve its compatibility and reactivity with other components in concrete, thereby effectively enhancing the strength of ceramsite;

[0022] 2. The addition of hydrogen peroxide increases the voids in the internal structure of ceramsite, making it lightweight. In addition, the addition of aluminum fluoride in the raw materials promotes the formation of mullite phase, thereby increasing the strength of ceramsite and reducing its damage rate;

[0023] 3. The present invention uses sodium silicate solution as an activator to soak the primary ceramsite, thereby promoting the pozzolanic reaction of oxides in fly ash, thereby further enhancing the strength of the ceramsite. DETAILED DESCRIPTION

[0024] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with embodiments.

[0025] The fly ash in all the embodiments and comparative examples of the present invention was purchased from Shengtong, the cement was purchased from Yapai, the lime was purchased from Yandong Haotian, the gypsum was purchased from Lanquan New Materials, the expanded perlite powder was purchased from Baixin, and the model of the titanate coupling agent was HY-201.

[0026] Example 1

[0027] A method for preparing steam-cured ceramsite from fly ash, wherein the method for preparing steam-cured ceramsite from fly ash comprises the following specific steps:

[0028] (1) First, the fly ash is calcined, then titanate is added and stirred, then the mixture is heated and dried, and sieved to obtain the pretreated fly ash;

[0029] (2) pre-treating fly ash, cement, lime, gypsum, expanded perlite powder, aluminum fluoride and hydrogen peroxide to form a mixture, and placing it in a round pot granulator, while spraying water on the surface of the mixture, the mass of the sprayed water is 10% of the mixture, and the mixture is rolled to obtain primary ceramsite;

[0030] (3) Soaking the primary ceramsite in an activator;

[0031] (4) After drying, curing and steaming, expanded clay is obtained.

[0032] The calcination temperature and time in step (1) are 800° C. and 20 min respectively, and the mass ratio of the titanate to the fly ash is 1:35, wherein the titanate is a titanate coupling agent.

[0033] The stirring speed and time in step (1) are 1200 r / min and 30 min respectively, the temperature and time of the heating and drying are 80° C. and 60 min respectively, and the mesh size of the sieving is 200 mesh.

[0034] In the step (2), the mass ratio of the pretreated fly ash, cement, lime, gypsum, expanded perlite powder, aluminum fluoride and hydrogen peroxide is 60:20:2:2:4:2:20, wherein the mass fraction of hydrogen peroxide is 60%.

[0035] In the step (2), the inclination and rotation speed of the round pot granulator are 35° and 33 r / min respectively.

[0036] The specific method of spraying water in step (2) is: one spray lasts about 1 second, each spray interval is 5 seconds, and the spraying lasts for 15 minutes. The rolling time of the mixture is 1 minute, and the particle size of the primary ceramsite is 4 mm.

[0037] The activator in step (3) is a sodium silicate solution with a mass fraction of 30%, and the soaking time is 30 minutes.

[0038] The specific method of drying in step (4) is: placing the primary ceramsite in an oven at 100° C. and drying for 1 hour, then taking it out and cooling it to room temperature.

[0039] The specific method of curing in step (4) is: placing the dried primary ceramsite in a place with light without moving it, and curing it naturally for 7 hours.

[0040] The specific method of steam curing in step (4) is: steam curing the cured primary ceramsite under high-temperature steam conditions of 120° C. for 6 hours.

[0041] Example 2

[0042] A method for preparing steam-cured ceramsite from fly ash, wherein the method for preparing steam-cured ceramsite from fly ash comprises the following specific steps:

[0043] (1) First, the fly ash is calcined, then titanate is added and stirred, then the mixture is heated and dried, and sieved to obtain the pretreated fly ash;

[0044] (2) pre-treating fly ash, cement, lime, gypsum, expanded perlite powder, aluminum fluoride and hydrogen peroxide to form a mixture, and placing it in a round pot granulator, while spraying water on the surface of the mixture, the mass of the sprayed water is 13% of the mixture, and the mixture is rolled to obtain primary ceramsite;

[0045] (3) Soaking the primary ceramsite in an activator;

[0046] (4) After drying, curing and steaming, expanded clay is obtained.

[0047] The calcination temperature and time in step (1) are 900° C. and 25 min respectively, and the mass ratio of the titanate to the fly ash is 1:40, wherein the titanate is a titanate coupling agent.

[0048] The stirring speed and time in step (1) are 1350 r / min and 35 min respectively, the temperature and time of the heating and drying are 90° C. and 80 min respectively, and the mesh size of the sieving is 300 meshes.

[0049] In the step (2), the mass ratio of the pretreated fly ash, cement, lime, gypsum, expanded perlite powder, aluminum fluoride and hydrogen peroxide is 70:30:6:7:6:3.5:25, wherein the mass fraction of hydrogen peroxide is 60%.

[0050] In the step (2), the inclination and rotation speed of the round pot granulator are 45° and 34 r / min respectively.

[0051] The specific method of spraying water in step (2) is as follows: one spray lasts about 1 second, each spray is 5 seconds apart, and the spray is continued for 15 minutes. The rolling time of the mixture is 1 minute, and the particle size of the primary ceramsite is 5 mm.

[0052] The activator in step (3) is a sodium silicate solution with a mass fraction of 38%, and the soaking time is 45 minutes.

[0053] The specific method of drying in step (4) is: placing the primary ceramsite in an oven at 110° C. and drying for 1.5 hours, then taking it out and cooling it to room temperature.

[0054] The specific method of curing in step (4) is: placing the dried primary ceramsite in a place with light without moving it, and curing it naturally for 8.5 hours.

[0055] The specific method of steam curing in step (4) is: steam curing the cured primary ceramsite under high-temperature steam conditions of 140° C. for 9 hours.

[0056] Example 3

[0057] A method for preparing steam-cured ceramsite from fly ash, wherein the method for preparing steam-cured ceramsite from fly ash comprises the following specific steps:

[0058] (1) First, the fly ash is calcined, then titanate is added and stirred, then the mixture is heated and dried, and sieved to obtain the pretreated fly ash;

[0059] (2) pre-treating fly ash, cement, lime, gypsum, expanded perlite powder, aluminum fluoride and hydrogen peroxide to form a mixture, and placing it in a round pot granulator, while spraying water on the surface of the mixture, the mass of the sprayed water is 15% of the mixture, and the mixture is rolled to obtain primary ceramsite;

[0060] (3) Soaking the primary ceramsite in an activator;

[0061] (4) After drying, curing and steaming, expanded clay is obtained.

[0062] The calcination temperature and time in step (1) are 1000° C. and 30 min respectively, and the mass ratio of the titanate to the fly ash is 1:45, wherein the titanate is a titanate coupling agent.

[0063] The stirring speed and time in step (1) are 1500 r / min and 40 min respectively, the temperature and time of the heating and drying are 100° C. and 90 min respectively, and the mesh size of the sieving is 400 meshes.

[0064] In the step (2), the mass ratio of the pretreated fly ash, cement, lime, gypsum, expanded perlite powder, aluminum fluoride and hydrogen peroxide is 80:40:14:10:8:5:30, wherein the mass fraction of hydrogen peroxide is 60%.

[0065] In the step (2), the inclination and rotation speed of the round pot granulator are 50° and 35 r / min respectively.

[0066] The specific method of spraying water in step (2) is as follows: one spray lasts about 1 second, each spray is separated by 5 seconds, and the spray is continued for 15 minutes. The rolling time of the mixture is 2 minutes, and the particle size of the primary ceramsite is 6 mm.

[0067] The activator in step (3) is a sodium silicate solution with a mass fraction of 45%, and the soaking time is 60 minutes.

[0068] The specific method of drying in step (4) is: placing the primary ceramsite in an oven at 120° C. and drying for 2 hours, then taking it out and cooling it to room temperature.

[0069] The specific method of curing in step (4) is: placing the dried primary ceramsite in a place with light without moving it, and curing it naturally for 10 hours.

[0070] The specific method of steam curing in step (4) is: steam curing the cured primary ceramsite under high-temperature steam conditions of 160° C. for 12 hours.

[0071] Comparative Example 1

[0072] On the basis of Example 2, a method for preparing steam-cured ceramsite from fly ash is provided. The method for preparing steam-cured ceramsite from fly ash comprises the following specific steps:

[0073] (1) adding titanate to fly ash and stirring, then heating and drying, and sieving to obtain pretreated fly ash;

[0074] (2) pre-treating fly ash, cement, lime, gypsum, expanded perlite powder, aluminum fluoride and hydrogen peroxide to form a mixture, and placing it in a round pot granulator, while spraying water on the surface of the mixture, the mass of the sprayed water is 13% of the mixture, and the mixture is rolled to obtain primary ceramsite;

[0075] (3) Soaking the primary ceramsite in an activator;

[0076] (4) After drying, curing and steaming, expanded clay is obtained.

[0077] In the step (1), the mass ratio of titanate to fly ash is 1:40, wherein the titanate is a titanate coupling agent.

[0078] The stirring speed and time in step (1) are 1350 r / min and 35 min respectively, the temperature and time of the heating and drying are 90° C. and 80 min respectively, and the mesh size of the sieving is 300 meshes.

[0079] In the step (2), the mass ratio of the pretreated fly ash, cement, lime, gypsum, expanded perlite powder, aluminum fluoride and hydrogen peroxide is 70:30:6:7:6:3.5:25, wherein the mass fraction of hydrogen peroxide is 60%.

[0080] In the step (2), the inclination and rotation speed of the round pot granulator are 45° and 34 r / min respectively.

[0081] The specific method of spraying water in step (2) is as follows: one spray lasts about 1 second, each spray is 5 seconds apart, and the spray is continued for 15 minutes. The rolling time of the mixture is 1 minute, and the particle size of the primary ceramsite is 5 mm.

[0082] The activator in step (3) is a sodium silicate solution with a mass fraction of 38%, and the soaking time is 45 minutes.

[0083] The specific method of drying in step (4) is: placing the primary ceramsite in an oven at 110° C. and drying for 1.5 hours, then taking it out and cooling it to room temperature.

[0084] The specific method of curing in step (4) is: placing the dried primary ceramsite in a place with light without moving it, and curing it naturally for 8.5 hours.

[0085] The specific method of steam curing in step (4) is: steam curing the cured primary ceramsite under high-temperature steam conditions of 140° C. for 9 hours.

[0086] Comparative Example 2

[0087] On the basis of Example 2, a method for preparing steam-cured ceramsite from fly ash is provided. The method for preparing steam-cured ceramsite from fly ash comprises the following specific steps:

[0088] (1) First, the fly ash is calcined and sieved to obtain pretreated fly ash;

[0089] (2) pre-treating fly ash, cement, lime, gypsum, expanded perlite powder, aluminum fluoride and hydrogen peroxide to form a mixture, and placing it in a round pot granulator, while spraying water on the surface of the mixture, the mass of the sprayed water is 13% of the mixture, and the mixture is rolled to obtain primary ceramsite;

[0090] (3) Soaking the primary ceramsite in an activator;

[0091] (4) After drying, curing and steaming, expanded clay is obtained.

[0092] The calcination temperature and time in step (1) are 900° C. and 25 min, respectively.

[0093] The mesh size of the sieving in step (1) is 300 meshes.

[0094] In the step (2), the mass ratio of the pretreated fly ash, cement, lime, gypsum, expanded perlite powder, aluminum fluoride and hydrogen peroxide is 70:30:6:7:6:3.5:25, wherein the mass fraction of hydrogen peroxide is 60%.

[0095] In the step (2), the inclination and rotation speed of the round pot granulator are 45° and 34 r / min respectively.

[0096] The specific method of spraying water in step (2) is as follows: one spray lasts about 1 second, each spray is 5 seconds apart, and the spray is continued for 15 minutes. The rolling time of the mixture is 1 minute, and the particle size of the primary ceramsite is 5 mm.

[0097] The activator in step (3) is a sodium silicate solution with a mass fraction of 38%, and the soaking time is 45 minutes.

[0098] The specific method of drying in step (4) is: placing the primary ceramsite in an oven at 110° C. and drying for 1.5 hours, then taking it out and cooling it to room temperature.

[0099] The specific method of curing in step (4) is: placing the dried primary ceramsite in a place with light without moving it, and curing it naturally for 8.5 hours.

[0100] The specific method of steam curing in step (4) is: steam curing the cured primary ceramsite under high-temperature steam conditions of 140° C. for 9 hours.

[0101] Comparative Example 3

[0102] On the basis of Example 2, the aluminum fluoride in step (2) was removed, and the other conditions were the same as those in Example 2.

[0103] Comparative Example 4

[0104] On the basis of Example 2, the hydrogen peroxide in step (2) was removed, and the other conditions were the same as those in Example 2.

[0105] Comparative Example 5

[0106] On the basis of Example 2, a method for preparing steam-cured ceramsite from fly ash is provided. The method for preparing steam-cured ceramsite from fly ash comprises the following specific steps:

[0107] (1) First, the fly ash is calcined, then titanate is added and stirred, then the mixture is heated and dried, and sieved to obtain the pretreated fly ash;

[0108] (2) pre-treating fly ash, cement, lime, gypsum, expanded perlite powder, aluminum fluoride and hydrogen peroxide to form a mixture, and placing it in a round pot granulator, while spraying water on the surface of the mixture, the mass of the sprayed water is 13% of the mixture, and the mixture is rolled to obtain primary ceramsite;

[0109] (3) After drying, curing and steaming, expanded clay is obtained.

[0110] The calcination temperature and time in step (1) are 900° C. and 25 min respectively, and the mass ratio of the titanate to the fly ash is 1:40, wherein the titanate is a titanate coupling agent.

[0111] The stirring speed and time in step (1) are 1350 r / min and 35 min respectively, the temperature and time of the heating and drying are 90° C. and 80 min respectively, and the mesh size of the sieving is 300 meshes.

[0112] In the step (2), the mass ratio of the pretreated fly ash, cement, lime, gypsum, expanded perlite powder, aluminum fluoride and hydrogen peroxide is 70:30:6:7:6:3.5:25, wherein the mass fraction of hydrogen peroxide is 60%.

[0113] In the step (2), the inclination and rotation speed of the round pot granulator are 45° and 34 r / min respectively.

[0114] The specific method of spraying water in step (2) is as follows: one spray lasts about 1 second, each spray is 5 seconds apart, and the spray is continued for 15 minutes. The rolling time of the mixture is 1 minute, and the particle size of the primary ceramsite is 5 mm.

[0115] The specific method of drying in step (3) is: placing the primary ceramsite in an oven at 110° C. and drying for 1.5 hours, then taking it out and cooling it to room temperature.

[0116] The specific method of curing in step (3) is: placing the dried primary ceramsite in a place with light without moving it, and curing it naturally for 8.5 hours.

[0117] The specific method of steam curing in step (3) is: steam curing the cured primary ceramsite under high-temperature steam conditions of 140° C. for 9 hours.

[0118] Comparative Example 6

[0119] On the basis of Example 2, the sodium silicate solution activator in step (3) is replaced by a sodium hydroxide solution with a mass fraction of 60%, and the other conditions are consistent with Example 2.

[0120] 1. Performance Testing

[0121] Compression strength test: Use the ceramsite prepared in Examples 1-3 and Comparative Examples 1-6 as samples, and gently place the samples into the pressure cylinder so that their volume is about 30% of the total volume of the cylinder. Use a small hammer to gently tap the cylinder wall. When the upper surface of the sample is basically horizontal, install the guide cylinder and the stamping die. Then tap the cylinder wall to make the scale line coincide with the stamping die and the stamping die coincide with the inner wall of the pressure cylinder. Use a pressure strength tester to uniformly descend at a rate of 300N / s until the depth of the stamping die is exactly 20mm, and stop descending. Note the pressure value on the display at this time, and take the average value after three consecutive tests;

[0122] Bulk density test: The ceramsite prepared in Examples 1-3 and Comparative Examples 3-4 was used as a sample and the bulk density test was performed according to SY / T5108-2006 and SY / T5108.

[0123] The above test results are shown in Table 1 and Table 2.

[0124] Table 1 Compressive strength test results

[0125] Sample Compression strength / MPa Example 1 30.71 Example 2 32.19 Example 3 29.10 Comparative Example 1 25.75 Comparative Example 2 23.10 Comparative Example 3 24.97 Comparative Example 4 21.89 Comparative Example 5 23.94 Comparative Example 6 26.40

[0126] Table 2 Bulk density test results

[0127] Sample <![CDATA[Bulk density / cm 3 > Example 1 1.35 Example 2 1.40 Example 3 1.42 Comparative Example 3 1.69 Comparative Example 4 1.72

[0128] It can be concluded from Table 1 and Table 2 that the compressive strength of Examples 1-3 is greater than that of Comparative Examples 1-6, among which the compressive strength of Comparative Example 4 is the smallest, and the volume density of Examples 1-3 is less than that of Comparative Examples 3-4. Comparative Example 1 does not calcine the fly ash, so its reaction activity is reduced. Comparative Example 2 does not add titanate for compound modification, so the reaction activity is also reduced. Comparative Example 3 does not add aluminum fluoride, which reduces the compressive strength. Comparative Example 5 removes the soaking step, and the oxides in the fly ash cannot be reacted, so the compressive strength is weaker than that of the embodiment. In Comparative Example 6, sodium hydroxide solution is used instead of sodium silicate solution, and the strong alkalinity of the sodium hydroxide solution weakens the compressive strength. In Comparative Examples 3-4, since aluminum fluoride or hydrogen peroxide is not added, the voids inside the ceramsite are reduced. Therefore, the volume density of the ceramsite of the embodiment is less than that of Comparative Examples 3-4, so that the ceramsite of the embodiment is lighter.

[0129] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing steam-cured ceramsite from fly ash, characterized in that: The method for preparing steam-cured ceramsite from fly ash comprises the following specific steps: (1) First, the fly ash is subjected to high-temperature treatment, and then titanate is added and stirred, and then the temperature is increased to dry, and sieved to obtain the pretreated fly ash; (2) pre-treating fly ash, cement, lime, gypsum, expanded perlite powder, aluminum fluoride and hydrogen peroxide to form a mixture, and placing it in a round pot granulator, while spraying water on the surface of the mixture, the mass of the sprayed water is 10-15% of the mixture, and the mixture is rolled to obtain primary ceramsite; (3) Soaking the primary ceramsite in an activator; (4) After drying, curing and steaming, expanded clay is obtained.

2. The method for preparing steam-cured ceramsite from fly ash according to claim 1, characterized in that: The calcination temperature and time in step (1) are 800-1000° C. and 20-30 min, respectively. The mass ratio of the titanate to the fly ash is 1:35-45, wherein the titanate is a titanate coupling agent.

3. The method for preparing steam-cured ceramsite from fly ash according to claim 1, characterized in that: The stirring speed and time in the step (1) are 1200-1500 r / min and 30-40 min respectively, the temperature and time of the heating and drying are 80-100° C. and 60-90 min respectively, and the mesh size of the sieving is 200-400 mesh.

4. The method for preparing steam-cured ceramsite from fly ash according to claim 1, characterized in that: In the step (2), the mass ratio of the pretreated fly ash, cement, lime, gypsum, expanded perlite powder, aluminum fluoride and hydrogen peroxide is 60-80:20-40:2-14:2-10:4-8:2-5:20-30.

5. The method for preparing steam-cured ceramsite from fly ash according to claim 1, characterized in that: In the step (2), the inclination and rotation speed of the round pot granulator are 35-50° and 33-35 r / min respectively.

6. The method for preparing steam-cured ceramsite from fly ash according to claim 1, characterized in that: The specific method of spraying water in step (2) is as follows: one spray lasts about 1 second, each spray is separated by 5 seconds, the rolling time of the mixture is 1-2 minutes, and the particle size of the primary ceramsite is 4-6 mm.

7. The method for preparing steam-cured ceramsite from fly ash according to claim 1, characterized in that: The activator in step (3) is a sodium silicate solution with a mass fraction of 30-45%, and the soaking time is 30-60 minutes.

8. The method for preparing steam-cured ceramsite from fly ash according to claim 1, characterized in that: The specific method of drying in step (4) is: placing the primary ceramsite in an oven at 100-120° C. and drying for 1-2 hours, then taking it out and cooling it to room temperature.

9. The method for preparing steam-cured ceramsite from fly ash according to claim 1, characterized in that: The specific method of curing in step (4) is: placing the dried primary ceramsite in a place with light without moving it, and curing it naturally for 7-10 hours.

10. The method for preparing steam-cured ceramsite from fly ash according to claim 1, characterized in that: The specific method of steam curing in step (4) is: steam curing the cured primary ceramsite under high temperature steam conditions of 120-160° C. for 6-12 hours.

Citation Information

Cited By

  • Method for preparing steam-cured ceramsite from high-content fly ash

    CN121083773A